2013
DOI: 10.1002/jmri.24008
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing MRI scan time in the computation of pharmacokinetic parameters (Ktrans) in breast cancer diagnosis

Abstract: Reducing the acquisition time for the K(trans) and ve measurement up to 60 seconds yields reasonable accuracy for both and can be incorporated in the routine DCE-MRI protocol for evaluation of enhancing breast lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
0
15
1
Order By: Relevance
“…230,231 The BM, which is particularly attractive since the AIF need not be known a priori, 232 has been used to study the brain 114,160,233 and breast tumors, 7,135,160,[233][234][235][236][237][238] as well as to analyze contrast uptake patterns in other applications, including intracranial meningiomas, 239 malignant pleural mesothelioma, 240 cervical cancer [241][242][243] and its chemoradiotherapy outcome, 232,244 colorectal 245 and liver tumors, 246 prostate diseases, 12,247,248 and bone perfusion. 185 The most straightforward PK models to interpret are the TK and ETK models, which have been extensively applied to characterize the brain, 3,115,175,249-255 lung, 256,257 breast, 200,[258][259][260][261][262][263][264][265][266][267][268][269] prostate, 13,…”
Section: E Clinical Applications Of Parametric Modelsmentioning
confidence: 99%
“…230,231 The BM, which is particularly attractive since the AIF need not be known a priori, 232 has been used to study the brain 114,160,233 and breast tumors, 7,135,160,[233][234][235][236][237][238] as well as to analyze contrast uptake patterns in other applications, including intracranial meningiomas, 239 malignant pleural mesothelioma, 240 cervical cancer [241][242][243] and its chemoradiotherapy outcome, 232,244 colorectal 245 and liver tumors, 246 prostate diseases, 12,247,248 and bone perfusion. 185 The most straightforward PK models to interpret are the TK and ETK models, which have been extensively applied to characterize the brain, 3,115,175,249-255 lung, 256,257 breast, 200,[258][259][260][261][262][263][264][265][266][267][268][269] prostate, 13,…”
Section: E Clinical Applications Of Parametric Modelsmentioning
confidence: 99%
“…More quantitative assessments can be made with the pharmacokinetic parameters of DCE-MRI, such as the trans-endothelial transfer constant (K trans ), the redistribution rate constant (K ep ), and the fractional volume (V e ) of the extravascular extracellular space (EES) (8). Several studies reported that quantitative DCE-MRI was able to differentiate malignant from benign brain, breast, and prostatic lesions with both high sensitivity and specificity (9)(10)(11). However, few studies have been performed using DCE-MRI for lung imaging because of the technical difficulties related to cardiorespiratory motion and its associated artifacts, which heavily influence the accuracy of the parameters (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…This makes them promising imaging biomarkers in multicenter clinical trials as imaging endpoints for standardization and comparison of results. However, the accuracy and precision of these parameters can be affected by a plethora of factors contributing to the process of pharmacokinetic modeling, including errors in quantification of precontrast T 1 ( 13 ) and determination of arterial input function (AIF) ( 14 20 ), inadequate temporal resolution ( 21 ), selection of pharmacokinetic models to fit the data ( 22 , 23 ), and differences in DCE-MRI acquisition time duration ( 24 , 25 ).…”
Section: Introductionmentioning
confidence: 99%